The impact of financial resource, human resource development practices and technological capability on SME performance in Sichuan, China - Xuanhai, Li (2024)
This study aims to deeply analyze the impact of financial resource, human resource development practices, and technology capabilities on the performance of small and medium-sized enterprises (SMEs) in Sichuan, China. Through a comprehensive review of relevant literature and empirical data analysis, it explores the interrelationships among these key factors and their combined effect on the growth of SMEs, providing important insights for enhancing the competitiveness and sustainable development of SMEs in the region. The research adopts a quantitative approach, targeting 600 SMEs in Sichuan. Data is collected through questionnaires and analyzed using methods such as descriptive analysis, reliability testing, mean analysis, and Pearson correlation analysis. The results show that there are significant positive correlations between financial resource, human resource development practises, technology capabilities, and SME performance, indicating that effective management and investment in these aspects are crucial for SMEs to improve performance. The findings of this study not only assist SME managers in formulating more scientific and reasonable development strategies but also provide targeted decision-making references for policymakers to promote the sustainable development of SMEs in finance, human resource development practises, and technology, thereby driving the prosperity and stability of the regional economy